Development of Recycled Media in SBdP Learning to Increase Student Learning Activity - Ramadhan, Anggy bagas; Institut Daarul Qur'an Jakarta, Putri Rahayu S; Institut Daarul Qur'an Jakarta, Zubaidi (Elementary Teacher Education Program, Majalengka University, 2024)
This research has a background, namely helping SBdP teacher MI Nurul Iman who lacks in developing recycled media. Therefore, to handle this matter, it is necessary to upgrade from what was originally inorganic waste to now a recycled media that can increase student learning activity. The aim of this research is to develop recycled media in SBdP learning to increase student learning activity. The research method used is Research and Development (R&D) which has Define, Design and Develop steps. The research respondents were 25 class V students of MI Nurul Iman, Tangerang City. The results of the research and product development produced show that 1) The development of waste recycling media can increase the learning activity of class V students and is beneficial for the surrounding environment and is good for forming children's character so that they care about the environment where they live; 2) Students responded very well during the recycling development trial process. This is because the results of the student response questionnaire were 88%. Because, with this recycled media students can be creative according to the student's creativity; 3) The use of recycled media in SBdP learning can increase student learning activity, which can be seen from the increase after and before using recycled media, the percentage of students who completed it reached 84% compared to 64% before using recycled media; 4) The importance of creative teachers can increase student activity by providing media that attracts student attention and increases activity in the learning process.